Vaginal delivery combined with vaginal tightening surgery and perineal body repair: 5 case reports - Wu, Hui (Medicine (Baltimore), 2020)
The present study aimed to investigate the feasibility of vaginal delivery combined with vaginal tightening surgery and perineal body repair. From January 2017 to April 2017, 5 cases underwent vaginal delivery combined with vaginal tightening surgery and perineal body repair. We retrospectively analyzed the clinical data. The incisions of 5 cases were all primary healing; vulva form was improved, and there were no postoperative hematoma, infection or vaginal mucosa prolapse. Sexual function was improved to different degrees. The pelvic muscle force test showed that both the type I and type II myofiber scores were increased. It is feasible to perform vaginal delivery combined with vaginal tightening surgery and perineal body repair, which is a safe and effective method for improving sex life and pelvic floor function.